VO₂max research: Endurance capacity levels of pencak silat martial artists - Ittaqwa; Triatmo Joko Purnomo; Widya Nur Afifa; Patrick Keilbart (spdfharmony.com, 2025)
Background: Low aerobic capacity remains a significant concern in combat sports, including pencak silat, as endurance is crucial in sustaining performance throughout a match. Martial artists lacking adequate aerobic fitness are more likely to experience performance decline in the later stages of competition. Aims: To determine their aerobic fitness profiles, this study will evaluate the maximal oxygen uptake (VO₂max) levels of pencak silat martial artists. Methods: A quantitative approach with a test-and-measurement design was employed, involving 12 pencak silat martial artists as research subjects. The primary instrument used was the Bleep test, a standardized tool for accurately assessing aerobic capacity. Result: The results showed that the martial artists' average VO₂max was 30.74 ml/kg/min, which falls into the low category. The categorization revealed that 50% of the martial artists were in the “very poor” category, 8.3% in “poor,” 25% in “fair,” and 16.7% in the “moderate” category. These findings indicate that the martial artists' aerobic fitness levels are still far from optimal, which may hinder their ability to perform at their best during competitions. Therefore, this study recommends implementing more structured and targeted training programs to improve aerobic capacity. Conclusion: Appropriate training interventions will enhance physical endurance and help maintain technical quality and consistent performance throughout matches. The results of this study offer valuable insights for coaches in designing more effective physical conditioning strategies.